2018
DOI: 10.1007/s12010-018-2771-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Fucosylated Trisaccharide Via Transglycosylation by α-l-Fucosidase from Thermotoga maritima

Abstract: Fucosylated oligosaccharides, such as 2'-fucosyllactose in human milk, have important biological functions such as prebiotics and preventing infection. In this work, the effect of an acceptor substrate (lactose) and the donor substrate 4-nitrophenyl-α-L-fucopyranoside (pNP-Fuc) on the synthesis of a fucosylated trisaccharide was studied in a transglycosylation reaction using α-L-fucosidase from Thermotoga maritima. Conducting a matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
0
22
1
1
Order By: Relevance
“…Tables , and list a variety of donor and acceptor substrates that have been used in transfucosylation reactions. The most commonly used acceptors are lactose, N ‐acetyl‐ d ‐lactosamine, pNP‐glycosides, and alcohols; however, the first two have greater relevance, since oligosaccharides similar to those in human milk have been synthesized from them . It has been reported that the presence of an aromatic amino acid in the active site of the fucosidase from T. maritima induces a preference for monosaccharide acceptors, in particular, pNP‐monosaccharides.…”
Section: Employment Of Fucosidases In the Synthesis Of Fucosylated Olmentioning
confidence: 99%
See 2 more Smart Citations
“…Tables , and list a variety of donor and acceptor substrates that have been used in transfucosylation reactions. The most commonly used acceptors are lactose, N ‐acetyl‐ d ‐lactosamine, pNP‐glycosides, and alcohols; however, the first two have greater relevance, since oligosaccharides similar to those in human milk have been synthesized from them . It has been reported that the presence of an aromatic amino acid in the active site of the fucosidase from T. maritima induces a preference for monosaccharide acceptors, in particular, pNP‐monosaccharides.…”
Section: Employment Of Fucosidases In the Synthesis Of Fucosylated Olmentioning
confidence: 99%
“…Furthermore, transfucosylation reactions demand an activated donor substrate, which means that the fucose moiety that is to be transferred, must form a high energy bond with a good leaving group, so that the energy provided by cleaving this bond contributes to lowering the activation energy in the transglycosylation reaction, for example, mono or disaccharides, a methyl group, a nitrophenyl group, and even some halogens, such as F. By far, the most reported substrate in transfucosylation reactions is pNP‐Fuc . One reason is that many fucosidases recognize this compound as a substrate.…”
Section: Employment Of Fucosidases In the Synthesis Of Fucosylated Olmentioning
confidence: 99%
See 1 more Smart Citation
“…As it can be seen in Table 1, 2 and 3 there is a wide variety of donor and acceptor substrates that have been used in transfucosylation reactions. The most common used acceptors are lactose, lactosamine, pNPglycosides and alcohols, however, the first two have greater relevance since oligosaccharides similar to those of human milk have been synthesized from these [36,[38][39][40]. It has been reported that the presence of the aromatic amino acid in the active site of the fucosidase of T. maritima induces a preference for monosaccharide acceptors in particular, pNP-monosaccharides.…”
Section: Donor and Acceptor Substratesmentioning
confidence: 99%
“…On the other hand, as explained above, transfucosylation reactions demand an activated donor substrate, what mean that fucose moiety to be transferred, needs to be linked to a molecule that ensure the easy cleave of the fucosidic bond, so this must molecule act as good leaving group during the reaction, for example, mono or disaccharides, methyl group, nitrophenyl group and even some halogens like F. By far, the most reported substrate in transfucoylation reactions is pNP-Fuc (2,(38)(39)(40)(41), first of all, because it is recognized as a substrate by many fucosidases, its characteristic of chromogenicity (releasing nitrophenol) makes it attractive in research it allows easily follow kinetics of hydrolysis by means of spectrophotometry, in addition is available in the market, in fact is one of the less expensive than many commercial fucosyl donor, since $150.00 to around $1,700.00 USD per gram depending on the seller. If it is true that pNP-Fuc is widely used as donor substrate in research, it has certain disadvantages such as low solubility in aqueous media and toxicity [44,45], which restrict it for certain purposes, for example synthesis of fucooligosaccharides oriented to food products.…”
Section: Donor and Acceptor Substratesmentioning
confidence: 99%